Flipped Book Based E-Module Interactive to Develop Meat Processing Technology Learning Media - Cakrawati, Dewi -; Fitri, Dewi -; Rahayu, Dwi Lestari (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2024)
The application of interesting learning media during the learning process is important to increase student enthusiasm which leads to increasing students’ cognitive results. This study aimed to develop meat processing technology learning media using a flipped-book based e-module interactive. Meat processing technology was one of the subjects for students in class XI Agribusiness vocational high school. The learning media was developed based on the research and development method by applying the ADDIE model that consists of five steps: Analysis, Design, Development, Implementation dan Evaluation. The learning media was validated by judgment experts namely computer teacher, language teacher, and subject-related teacher. The instruments used for validation were questionnaires with a Likert scale from 1-to 4. Judgment expert validation showed the learning media was qualified based on content (95.45%), language (95.83%), and features (86.67%). Features of media had the lowest grade according to judgment experts since several improvements were needed namely repairing the media cover, changing the font color to brighter color, give different colors to the font to differentiate the menu in the e-module. The media was improved based on suggestions from judgment experts before being used as learning media for meat processing technology subjects.